2017
DOI: 10.1016/j.rehab.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tendon vibration reduces the increased facilitation from quadriceps to soleus in post-stroke hemiparetic individuals

Abstract: Patellar tendon vibration can reduce the facilitation between knee and ankle extensors, which suggests effective presynaptic inhibition but decreased post-activation depression in the lower limb of people after chronic hemiparetic stroke. Further studies are warranted to determine whether such vibration could be used to reduce the abnormal extension synergy of knee and ankle extensors in people after hemiparetic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The primary focus has been on the magnitude of heteronymous excitation because excessive excitation could contribute to the abnormal Q and SOL coactivation frequently observed in stroke survivors during walking (3). In support of this premise, one research group observed abnormally increased heteronymous excitation in persons with stroke from Q onto the SOL Hre ex (4) and ongoing tonic SOL EMG (5,7). In contrast, the present study found that femoral nerve elicited heteronymous excitation measured as change in tonic SOL EMG was not greater in the paretic compared to the nonparetic or age-matched control limbs.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The primary focus has been on the magnitude of heteronymous excitation because excessive excitation could contribute to the abnormal Q and SOL coactivation frequently observed in stroke survivors during walking (3). In support of this premise, one research group observed abnormally increased heteronymous excitation in persons with stroke from Q onto the SOL Hre ex (4) and ongoing tonic SOL EMG (5,7). In contrast, the present study found that femoral nerve elicited heteronymous excitation measured as change in tonic SOL EMG was not greater in the paretic compared to the nonparetic or age-matched control limbs.…”
Section: Discussionsupporting
confidence: 75%
“…Lower limb heteronymous re exes can in uence motor coordination because excitatory and inhibitory feedback from a muscle can increase and decrease motor output of other muscles (8-12, 15, 17, 18, 25, 31, 33, 34). Therefore, abnormal lower limb motor coordination such as Q and SOL coactivation frequently observed after stroke during walking could arise, in part, from alterations to the strength of excitatory and inhibitory heteronymous feedback (4)(5)(6)(7)13). This study examined whether persons with stroke exhibit sensorimotor impairments in heteronymous excitation and inhibition from Q onto SOL, and whether heteronymous re ex magnitudes are related to lower limb motor impairment, walking speed, and dynamic balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 In addition, a clinical study has shown that the vibration applied to the sole of the foot of patient after stroke has a positive effect on balance improvement, 10 and another study has shown that patellar tendon vibration can reduce pathological extensor synergy after stroke. 11 However, it is difficult to compare the effects of vibration on the human body through the results of previous studies, because the vibration characteristics (such as the type, frequency, and intensity) used in each study are different. Therefore, a quantitative standard for the effect of vibration stimulus is needed, and it can be found through the change of Mu rhythm activity according to vibratory stimulus.…”
Section: Introductionmentioning
confidence: 99%